The Role of Neurokinin-1 Receptor in the Microenvironment of Inflammation and Cancer - Marisa Rosso; Miguel Muñoz; Michael Berger (The Scientific World Journal)
The recent years have witnessed an exponential increase in cancer research, leading to a considerable investment in the field. However, with few exceptions, this effort has not yet translated into a better overall prognosis for patients with cancer, and the search for new drug targets continues. After binding to the specific neurokinin-1 (NK-1) receptor, the peptide substance P (SP), which is widely distributed in both the central and peripheral nervous systems, triggers a wide variety of functions. Antagonists against the NK-1 receptor are safe clinical drugs that are known to have anti-inflammatory, analgesic, anxiolytic, antidepressant, and antiemetic effects. Recently, it has become apparent that SP can induce tumor cell proliferation, angiogenesis, and migration via the NK-1 receptor, and that the SP/NK-1 receptor complex is an integral part of the microenvironment of inflammation and cancer. Therefore, the use of NK-1 receptor antagonists as a novel and promising approach for treating patients with cancer is currently under intense investigation. In this paper, we evaluate the recent scientific developments regarding this receptor system, its role in the microenvironment of inflammation and cancer, and its potentials and pitfalls for the usage as part of modern anticancer strategies.